2011
DOI: 10.1016/s0034-7094(11)70070-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inhalational Anesthetics Halothane and Sevoflurane on an Experimental Model of Hepatic Injury

Abstract: Compared to the halothane group, sevoflurane did not show injuries of the liver parenchyma on optical microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…8,9 Previous studies have shown that sevoflurane at clinical concentrations is not detrimental to liver and renal function. However, sevoflurane undergoes very little hepatic metabolism, and its metabolites are less reactive than those of other halogenated anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous studies have shown that sevoflurane at clinical concentrations is not detrimental to liver and renal function. However, sevoflurane undergoes very little hepatic metabolism, and its metabolites are less reactive than those of other halogenated anaesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some authors affirm that the transaminases' values were slightly increased after inhaled anesthesia with sevoflurane (Soubhia et al, 2011). Some of them write that isoflurane and sevoflurane anesthesia induces an increase in the seric concentration of hepatic enzymes, isoflurane inducing a greater increase in comparison to sevoflurane (Nishiyama, 2013), while others write that the seric level of aspartate-aminotranferase (ASAT) slightly increased in the first day after sevoflurane anesthesia (Sun et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our results, integrity of tissue was intact in all groups, although spermatogonial cells population decreased in experimental group 2. Soubhia et al evaluated the effect of sevoflurane on transaminase on liver histology ( 23 ). Also, Elena et al studied some organs like spleen, kidney and liver after repeated sevoflurane anesthesia ( 24 ).…”
Section: Discussionmentioning
confidence: 99%